Integration of Ethnomathematics Teaching Materials in Mathematics Learning in Elementary School - Deah Uji Wulandari; Neni Mariana; Wiryanto Wiryanto; Mohammad Sulthon Amien (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research serves as a preliminary study to outline the framework and projection of ethnomathematics studies, particularly concerning the integration of ethnomathematics into mathematics curriculum and the development of mathematics learning objectives using an ethnomathematical approach. Method: The research employs a Systematic Literature Review (SLR) methodology involving identifying, evaluating, and interpreting relevant literature on the research topic. Results: The findings reveal that the ethnomathematical approach effectively enhances students' understanding of mathematics. Students exhibit higher motivation and satisfaction with mathematics learning when connected to their local culture. Novelty: This research shows that the ethnomathematics approach facilitates the development of teachers' competencies in integrating cultural elements into mathematics education. Both teachers' recommendations and research findings support the inclusion of ethnomathematics in mathematics curricula both directly in developing learning tools and materials and in curriculum policies. Additionally, there is potential for technology applications to support ethnomathematics learning, enabling students to study mathematics independently. In conclusion, integrating ethnomathematics holds significant potential in improving students' mathematical understanding, connecting mathematics with local culture, and motivating students to learn mathematics more enjoyable and relevantly.